CLINICAL SYMPTOMS, MODERN EXAMINATION METHODS AND TREATMENT PRINCIPLES OF LABYRINTH DISEASE - Kurdasheva Ruhshona Bahodir qizi; Sultonbayeva Ruxsora Xudayshukur qizi; Diliyeva Shahnoza Ibrogim qizi; Masharipova Dilfuza Gʻofurjon qizi; Oʻrinova Sevinch Murodali qizi (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
In this article, special attention is paid to clarifying the factors causing labyrinthitis, pathogenesis, specific clinical signs, important diagnostic factors in the diagnosis of the disease, and modern principles of treatment.